Lost in lockdown? COVID-19, social distancing, and mental health in Germany - Stephanie Armbruster; Valentin Klotzbücher (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2020)
The COVID-19 pandemic and social-distancing and stay-at-home orders can directly affect mental health and quality of life. In this ongoing project, we analyze rich data from Telefonseelsorge, the largest German helpline service, to better understand the effect of the pandemic and of local lockdown measures on mental health-related helpline contacts. First, looking at Germany-wide changes, we find that overall helpline contacts increase by around 20% in the first week of the lockdown and slowly decrease again after the third lockdown week. Our results suggest that the increase is not driven by financial worries or fear of the virus itself, but reflects heightened loneliness, anxiety, and suicidal ideation. Second, we exploit spatial variation in policies among German federal states to assess whether the effect depends on the stringency of local measures. Preliminary evidence suggests that the average effect is more pronounced in states that implemented stricter measures.
Keywords: I12; I3; 330; COVID-19; Stay-at-Home Orders; Mental Health